Microvascular dysfunction is associated with impaired myocardial work in obstructive and nonobstructive hypertrophic cardiomyopathy: a multimodality approach. (3rd October 2022) - Garcia Bras, P; Cardoso, I; Aguiar Rosa, S; Moura Branco, L; Galrinho, A; Valentim Goncalves, A; Thomas, B; Fiarresga, A; Mota Carmo, M; Branco, G; Pereira, R; Selas, M; et al.
Abstract: Introduction: Myocardial work is a dynamic non-invasive method for assessing myocardial deformation. Microvascular dysfunction is a hallmark of hypertrophic cardiomyopathy (HCM). We hypothesized that there is an association between impaired myocardial work, evaluated by echocardiography, and left ventricular (LV) ischemia, detected by cardiac magnetic resonance (CMR). Methods: Prospective assessment of HCM patients' (P) myocardial strain parameters with 2D speckle-tracking echocardiography. All P underwent CMR protocol (1.5-T) for the analysis of stress perfusion and late gadolinium enhancement (LGE). Perfusion defects were quantified as burden of ischemia (% of LV mass). Results were stratified according to obstructive (oHCM) and nonobstructive (nHCM) HCM as well as according to the presence of significant replacement fibrosis (LGE of ≥15% or <15% of LV mass). Multivariate regression analyses were used to explore the relation between myocardial work and the burden of ischemia. Results: 75 P with HCM (63% male, age 55±15 years), 61% with asymmetric septal LVH, 29% with apical LVH, 8% with concentric LVH and 28% exhibiting LV outflow tract obstruction (mean maximal LVOT gradient of 89±60 mmHg). Perfusion defects were found in 68 P (90.7%), with a mean of 22.5±16.9% of LV mass and 29 P (38.7%) had LGE ≥15% of LV mass. A lower global work index (GWI) significantly correlated with higher burden of myocardial perfusion defects (r=−0.520, β-estimate −0.019, 95% CI −0.028 to −0.010, p<0.001). Likewise, impaired values of global work efficiency (GWE) were linked to higher percentage of hypoperfusion (r=−0.477, β-estimate −0.713, 95% CI −1.250 to −0.176, p<0.001). Moreover, impaired global constructive work (GCW) (r=−0.519, β-estimate −0.021, 95% CI −0.030 to −0.013, p<0.001) and a higher global wasted work (GWW) (r=0.280, p=0.017) were associated with a higher burden of perfusion defects (Figure 1). GWI showed a higher correlation with perfusion defects in oHCM P (r=−0.518, p=0.019) vs. nHCM P (r=−0.492, p<0.001), and the same was also found with GWE (oHCM: r=−0.591, p=0.006 vs. nHCM: r=−0.317, p=0.022) (Figure 2A). Furthermore, GCW showed a slightly higher correlation with hypoperfusion in oHCM P (r=−0.564, p=0.010) vs. nHCM P (r=−0.520, p<0.001). There was no significant difference between oHCM and nHCM P regarding GWW. In P with LGE ≥15%, GWI showed a better correlation with perfusion defects (r=−0.489, p=0.007) vs. P with LGE of <15% (r=−0.369, p=0.007). Moreover, GCW showed a higher correlation with hypoperfusion in P with LGE ≥15% (r=−0.455, p=0.013) comparing with P with LGE <15% LV mass (r=−0.359, p=0.019) (Figure 2B). No difference was found regarding GWE and GWW according to LGE burden. Conclusion: In our cohort of P with HCM, impaired GWI, GWE and GCW and a higher GWW were significantly correlated with the presence of myocardial ischemia in CMR. This correlation was greater in P with oHCM and in P with LGE of ≥15% of LV mass. Funding Acknowledgement: Type of funding sources: None.